MUSICAL CHARM OF M. STEPANENKO IN THE EDUCATIONAL PROCESS (Pedagogy of Higher and Secondary Education, 2009)
The author considers features of musical language planistic M. Stepanenko's products, use of the basic means of musical expressiveness for a complete reconstruction of figurative dramatic art of the musical text.
Keywords: composer; play; musical language; melody dynamics; musical figurativeness